Os crimes de mídia no paradigma democrático constitucional - Holanda, Kildare de Medeiros Gomes (2013)
The criminal responsibility of the media is analyzed when the criteria for production of news and events involving public safety are produced without considering the technical, legal and ethical practice of journalism in the media factors. Freedom of speech, expression of thought, necessary for professional qualifications and constitutional limits, reaching criminal constitutional principles and the possibilities of criminal liability for offenses practiced in the media are present as key factors legal dialogue in this work. The judgment of the Supreme Court on the unconstitutionality of Law nº. 5.250/67 called Media Law caused a gap in the national legal system, forcing the use of the criminal code to address issues that involve crimes produced in media professional performance. The presumption of innocence is ignored by the professional media during a police investigation where the information published does not respect, including constitutional guarantees: the right to privacy, honor and image. The right to information and the duty to inform media are worked in its constitutional aspect, considering that the same information should be produced is guided by the quality and guiding principles of truth. The constitutional concept of media is presented as information with the appropriate language of the news media, produced and disseminated through the vehicles of mass media, whether in print or digital platform. The presented model of the legal right to information is outlined from a constitutional hermeneutics, increasing the production of news as a result of the occupation of journalist in different news platforms, guaranteeing the quality of this prolific law. Under the Freedom of professional activity of the journalist, the constitutional limits are addressed in line with the reality of (non) regulation of their profession, considering the constitutional abuses committed in the exercise of that activity linked to communication fences. Jusphilosophic field reaches the limits of the duty of truth in journalism as a tool for spreading news, respect the audience and compatibility with the constitutional state. Using the conceptual and doctrinal aspects, this criminal offense is parsed from the journalistic practice and the publication of news involving public safety, with the hypothetical field consummation of that crime through the eventual intention. As a form of judgment against these crimes produced in honor media presents the court of the jury as a legitimate form of democratic decision